Application Of Human Values In Achieve The Organization's Vision - Alan Ardiansah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The study of human values is an interesting thing because it relates to human life. In human life, values, morals and law cannot be separated. In fact, problems in human life occur when there is no longer the role of values, morals and law in life. Values are a very important foundation that regulates all human behavior. Values are a source of strength in upholding social order and regularity. Thus, morals are the basis of human behavior which makes life run according to humanist-religious norms of life. The power of law is a control in regulating justice regarding the rights and obligations of every human being in carrying out important roles for human life. The role of values, morals and law is an important part of the process of forming the character of a nation. A good organization requires the application of good values, especially so that it can carry out its mission smoothly so that the expected vision is achieved. Values that can be applied include: Integrity, professionalism, accountability, innovation and caring.